Source localization of ictal SEEG to predict postoperative seizure outcome. (December 2022) - Satzer, David; Esengul, Yasar T.; Warnke, Peter C.; Issa, Naoum P.; Nordli, Douglas R.
Highlights: SEEG source localization allowed accurate representation of the seizure onset zone in three-dimensional space. Concordance of dipoles with the treatment volume predicted seizure outcome. Near-field recordings were necessary for accurate SEEG source localization. Abstract: Objective: Stereo-electroencephalography (SEEG) is inherently-three-dimensional and can be modeled using source localization. This study aimed to assess the validity of ictal SEEG source localization. Methods: The dominant frequency at ictal onset was used for source localization in the time and frequency domains using rotating dipoles and current density maps. Validity was assessed by concordance with the epileptologist-defined seizure onset zone (conventional SOZ) and the surgical treatment volume (TV) of seizure-free versus non-seizure-free patients. Results: Source localization was performed on 68 seizures from 27 patients. Median distance to nearest contact in the conventional SOZ was 7 (IQR 6–12) mm for time-domain dipoles. Current density predicted ictal activity with up to 86 % (60–87 %) accuracy. Distance from time-domain dipoles to the TV was smaller (P = 0.045) in seizure-free (2 [0–4] mm) versus non-seizure-free (12 [2–17] mm) patients, and predicted surgical outcome with 91 % sensitivity and 63 % specificity. Removing near-field data from contacts within the TV negated outcome prediction (P = 0.51). Conclusions: Source localization of SEEG accurately mapped ictal onset compared with conventional interpretation. Proximity of dipoles to the TV predicted seizure outcome when near-field recordings were analyzed. Significance: Ictal SEEG source localization is useful in corroborating the epileptogenic zone, assuming near-field recordings are obtained.